2021
DOI: 10.1177/08971900211004828
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Fever Associated With Dexmedetomidine in the Adult Intensive Care Unit

Abstract: Background: Published literature has described the temporal relationship of dexmedetomidine with elevated temperatures, but there is limited data to quantify the incidence of fever in ICU patients receiving dexmedetomidine. Objective: The primary objective of this study was to estimate the incidence of temperature greater than or equal to 38.5°C in ICU patients receiving dexmedetomidine. Methods: This was a retrospective cohort study of ICU patients who received dexmedetomidine with a propensity-matched subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…9 In a retrospective cohort study of adult ICU patients across two tertiary hospitals, 15.1% of patients that received six or more hours of dexmedetomidine continuous infusions had at least one temperature greater than or equal to 38.5°C. 6 The mean maximum temperature of these patients was 38.9°C with a mean time from dexmedetomidine initiation to fever onset of 26.5 hours. In a retrospective cohort study across medical and surgical ICUs at a single institution, patients exposed to dexmedetomidine had a strong association for temperatures ≥103.1°F (39.5°C) compared to patients not exposed to dexmedetomidine (OR: 4.5; CI: 3.4, 5.9; P < .001).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…9 In a retrospective cohort study of adult ICU patients across two tertiary hospitals, 15.1% of patients that received six or more hours of dexmedetomidine continuous infusions had at least one temperature greater than or equal to 38.5°C. 6 The mean maximum temperature of these patients was 38.9°C with a mean time from dexmedetomidine initiation to fever onset of 26.5 hours. In a retrospective cohort study across medical and surgical ICUs at a single institution, patients exposed to dexmedetomidine had a strong association for temperatures ≥103.1°F (39.5°C) compared to patients not exposed to dexmedetomidine (OR: 4.5; CI: 3.4, 5.9; P < .001).…”
Section: Discussionmentioning
confidence: 84%
“…[2][3][4] As the clinical use of dexmedetomidine has increased with the drug becoming generic, recent reports have associated dexmedetomidine with low-grade fever. 5,6 Here, we present the case of severe hyperthermia that developed within hours of initiating dexmedetomidine infusion in a critically ill patient.…”
Section: Introductionmentioning
confidence: 99%
“…Recent case series, case reports, and a post hoc analysis have all suggested a link between dexmedetomidine use and hyperthermia. 5,6,[8][9][10][11][12][13] A post hoc analysis of the patients included in the Sedation Practice in Intensive Care Evaluation (SPICE) III study showed that over the first 5 ICU days more patients had a temperature greater than or equal to 38.3°C in the dexmedetomidine group compared to the usual care group (43.3% vs 32.7%; P = .004). 9,14 There was no difference found in the mean daily temperature between the dexmedetomidine group vs the usual care group (36.84°C vs 36.78°C; P = .16); however, this study found a significant difference in the highest daily temperature between the dexmedetomidine group and the usual care group (37.41°C vs 37.29°C; P = .01).…”
Section: Introductionmentioning
confidence: 99%